Reclaiming Degraded Rainforest: A Spatial Evaluation of Gains and Losses in Subtropical Eastern Australia to Inform Future Investment in Restoration. Issue 4 (27th September 2012) - Shoo, Luke P.; Scarth, Peter; Schmidt, Susanne; Wilson, Kerrie A.
Abstract Forest restoration is expected to play a pivotal role in reducing extinctions driven by deforestation and climate change over the next century. However, spatial and temporal patterns of restoration (both passive and active) are likely to be highly variable depending on degree of land use change as well as levels of forest and soil degradation and residual vegetation. Uncertainties regarding the spatial and temporal reinstatement of forest on degraded land make it difficult to determine where future investment in active restoration should be targeted. We used satellite data to quantify change in the extent and foliage projection cover (FPC) of woody vegetation returning to land previously cleared of subtropical rainforest in eastern Australia. We show a modest recovery of woody vegetation but document high variability in this trend between local areas, expanding by over 5% in some situations but declining by up to 2% in others over the last decade (1999–2009 period). This was accompanied by minor change in average FPC (−0.2 to 4.2%). Overall, decadal expansion in woody vegetation was most apparent in local areas with intermediate levels of existing forest reestablishment and was most likely to occur on steep terrain near existing vegetation. These results provide a valuable first evaluation of where restoration is occurring and the likely time frame required to meet conservation objectives under a business as usual scenario. This knowledge enables returns from current investment to be quantified and can be used to better allocate funds for restoration in the future.